2022
DOI: 10.4103/sjg.sjg_499_21
|View full text |Cite|
|
Sign up to set email alerts
|

Rate and risk factors of postoperative endoscopic recurrence of moderate- to high-risk Crohn's disease patients - A real-world experience from a Middle Eastern cohort

Abstract: Background: Crohn's disease (CD) frequently recurs after intestinal resection. Azathioprine (AZA) and biological therapies have shown efficacy in preventing postoperative recurrence (POR). Data on POR from Middle Eastern populations is lacking. This study aimed to evaluate the rate of endoscopic POR in a cohort of CD patients who underwent ileocecal resection (ICR), and to assess the effectiveness of AZA and biological therapies in reducing the risk of disease recurrence. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Of the 22 articles, 12 were from Europe [ 13 , 18 20 , 22 25 , 30 , 36 ], 4 from North America [ 21 , 26 , 27 , 29 ], 5 from Asia [ 14 , 15 , 28 , 34 , 35 ], and 1 from South America [ 17 ]. The results demonstrated that the ePOR rate was [ES = 0.55, 95% CI (0.47, 0.63)] in Europe, [ES = 0.24, 95% CI (0.13, 0.35)] in North America, [ES = 0.53, 95% CI (0.32, 0.73)] in Asia, and [ES = 0.34, 95% CI (0.26, 0.42)] in South America.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 22 articles, 12 were from Europe [ 13 , 18 20 , 22 25 , 30 , 36 ], 4 from North America [ 21 , 26 , 27 , 29 ], 5 from Asia [ 14 , 15 , 28 , 34 , 35 ], and 1 from South America [ 17 ]. The results demonstrated that the ePOR rate was [ES = 0.55, 95% CI (0.47, 0.63)] in Europe, [ES = 0.24, 95% CI (0.13, 0.35)] in North America, [ES = 0.53, 95% CI (0.32, 0.73)] in Asia, and [ES = 0.34, 95% CI (0.26, 0.42)] in South America.…”
Section: Resultsmentioning
confidence: 99%
“…Of the included 23 studies published from 2015 to 2023, 5 were case-control studies [13][14][15][16][17] and 18 were cohort studies [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Among them, 3 were from the Netherlands [19,20,33], 3 each from Italy [13,23,24] and China [15,28,31], 4 each from France [18,25,30,32] and the United States [21,26,27,29], and 1 each from Korea [14], Belgium [22], Portugal [16], Japan [34], Israel [35], and Brazil [17].…”
Section: Basic Featuresmentioning
confidence: 99%
“…Azathioprine is commonly used as an immunosuppressant for treating CD and may not increase the risk of postoperative complications. Although azathioprine has demonstrated efficacy in preventing postoperative recurrence, there is no significant decrease in the need for surgery or intestinal complications from CD[ 71 , 72 ] (Table 1 ). Furthermore, CD patients are frequently treated with steroids before surgery.…”
Section: Clinical Factors Affecting Timing Of Surgerymentioning
confidence: 99%
“…In the article titled “Rate and risk factors of postoperative endoscopic recurrence of moderate- to high-risk Crohn’s disease patients - A real-world experience from a Middle Eastern cohort”, published on pages 201-208, Issue 3, Volume 28, of Saudi Journal of Gastroenterology [ 1 ], the affiliation for authors “Nahla Azzam, Abdulla Al Thaher, Othman Alharbi, Mansour Altuwaijri, Suliman Alshankiti, Mohammed Alanazi, Abdulelah Alanazi and Abdulrahman Aljebreen, is incorrectly written as “Department of Medicine, King Saud University Medical City, Riyadh, Kingdom of Saudi Arabia.”…”
mentioning
confidence: 99%